Exploration of Mathematical Communication Skills of Students with Mild Intellectual Disability Through Manipulative Activities Using Bowls and Marbles - Muchyidin, Arif; Priatna, Nanang; Nurjanah (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
This study identified students' mathematical understanding and communication deficiencies, especially in dividing numbers. Although bowls and marbles have been used to support mathematical conceptual understanding, there are limitations in understanding how students communicate effectively about division and numbers in practical contexts. This study explores students' mathematical communication skills in dividing and counting and how using bowls and marbles influences this. The research method used is a case study with a qualitative approach involving direct observation and video recording. The study subjects comprised four students with mild intellectual disabilities and different characteristics in communicating and understanding mathematical concepts. The instruments used included observation notes and video recordings of learning. Data were collected through observation of the learning process and video analysis to assess communication skills and conceptual understanding. The results showed that students 1 and 2 had better mathematical communication skills and a strong understanding of division, although with some initial errors. Students 3 and 4 highly depended on teacher direction and were less active in verbal communication. This study concludes that using bowls and marbles can improve understanding of division, but the success of mathematical communication is greatly influenced by active student involvement and teacher direction. This study implies the need to develop more interactive learning strategies and additional support for students with difficulties in mathematical communication. Applying teaching techniques emphasizing active student involvement and effective use of bowls and marbles can improve understanding of mathematical concepts and communication skills. Penelitian ini mengidentifikasi kekurangan dalam pemahaman dan komunikasi matematis siswa, terutama dalam konteks pembagian bilangan. Meskipun bowls and marbles telah digunakan untuk mendukung pemahaman konsep matematis, terdapat keterbatasan dalam memahami bagaimana siswa berkomunikasi secara efektif mengenai pembagian dan membilang dalam konteks praktis. Penelitian ini bertujuan untuk mengeksplorasi kemampuan komunikasi matematis siswa dalam konteks pembagian dan membilang serta bagaimana hal ini dipengaruhi oleh penggunaan mangkok dan kelereng. Metode penelitian yang digunakan adalah studi kasus dengan pendekatan kualitatif, melibatkan observasi langsung dan rekaman video. Subjek penelitian terdiri dari empat siswa tunagrahita ringan dengan karakteristik berbeda dalam berkomunikasi dan memahami konsep matematika. Instrumen yang digunakan meliputi catatan observasi dan rekaman video pembelajaran. Data dikumpulkan melalui observasi proses pembelajaran dan analisis video untuk menilai kemampuan komunikasi dan pemahaman konsep. Hasil penelitian menunjukkan bahwa siswa 1 dan siswa 2 memiliki kemampuan komunikasi matematis yang lebih baik dan pemahaman yang kuat mengenai pembagian, meskipun dengan beberapa kesalahan awal. Siswa 3 dan siswa 4 menunjukkan ketergantungan yang tinggi pada arahan guru dan kurang aktif dalam komunikasi verbal. Kesimpulan dari penelitian ini adalah bahwa media manipulatif dapat meningkatkan pemahaman pembagian, namun keberhasilan komunikasi matematis sangat dipengaruhi oleh keterlibatan aktif siswa dan arahan guru. Implikasi dari penelitian ini adalah perlunya pengembangan strategi pembelajaran yang lebih interaktif dan dukungan tambahan bagi siswa yang menunjukkan kesulitan dalam komunikasi matematis. Penerapan teknik pengajaran yang menekankan pada keterlibatan siswa secara aktif dan penggunaan media manipulatif yang efektif dapat meningkatkan pemahaman konsep matematis dan keterampilan komunikasi.